Kewenangan KPK dalam Penyelidikan terhadap Kerahasiaan Bank - Naufal Ihsan; Okky Dila Haznianto; Alhamdani Derry Hafidzy; Wahyu Nursehan (Departement of Islamic Banking, Faculty of Islamic Economics and Business, The State of Islamic University (UIN) Sultan Maulana Hasanuddin Banten, 2021)
The principle of bank secrecy adopted by banks on the one hand is very beneficial for customers because all information is maintained safely, while on the one hand it can harm certain parties who in urgent need of financial data of these customers. However, in Indonesia, bank secrecy can still be opened or penetrated by certain things based on provisions in the Banking Law and outside the Banking Law, one of which is the Corruption Eradication Commission (KPK). If carried out properly, the KPK wiretapping will be of higher quality because there are those who supervise and have to make reports. The wiretapping arrangement in Law No. 19 of 2019 concerning Amendments to Law No. 30 of 2002